Massive Acquired Renal Cysts Presenting with Bowel Obstruction-Like Symptoms - Chutikarn Teparak; Weeratian Tawanwongsri (Case Reports in Medicine)
Acquired cystic kidney disease (ACKD) is rarely massive in size. The great majority is asymptomatic and incidentally found on imaging studies for unrelated causes. We reported a case of an 85-year-old male with bilateral multiple huge acquired renal infected cysts, initially presenting with bowel obstruction-like symptoms. The computed tomography (CT) scan later aided in an accurate diagnosis. Symptomatic huge ACKD has, to our knowledge, scarcely been described. In addition, retroperitoneal lesions resulting in abdominal pain remain unusual and underrecognized in general practice.